Pilot study of the productivity and Salmonella seroprevalence in pigs administered organic acids - Roldan-Henao, Manuela; Dalsgaard, Anders; Cardona-Castro, Nora; Restrepo-Rivera, Lina; Veloza-Angulo, Luis Carlos; Alban, Lis (Frontiers in Veterinary Science, 2023)
Control of Salmonella in pig/pork production is essential to protect public health because pork is one of the sources of human infection. Moreover, antimicrobial use in pig farms should be kept low to minimize the development of antimicrobial resistance. This pilot study evaluated the productivity and Salmonella prevalence in pigs administered organic acids (OA) compared to pigs given growth promoters in one farm in Antioquia, Colombia. Two groups, each consisting of 60 pigs six weeks of age, were studied for four months. One group was provided feed and water with OA (Selko pH® and Selacid®), whereas the other group (control) received antimicrobial growth promoters (tylosin and zinc bacitracin). Blood samples were taken three times (T1-T3), and pigs were weighted five times to calculate daily weight gain (DWG) and feed conversion ratio (FRC). Initially, the Salmonella seroprevalence was 1.7% in both groups. At T2, the seroprevalence was significantly lower in pigs provided OA compared to the control group (19% vs. 47%, P<0.01), whereas at T3, the seroprevalence was similar (62% vs. 77%; P=0.075) in both groups. The cumulative DWG was significantly higher in the intervention group than in the control group (713g/day vs. 667g/day; P<0.001). FCR did not differ between groups (2.80 vs. 2.77; P=0.144). The pilot study indicates that the OA administration could improve pigs' productivity and delay exposure to Salmonella spp. when compared to growth promoters. Hence, to lower antimicrobial use and resistance, OA could replace growth promoters. However, the study should be repeated before coming to firm conclusions.